8-epi-Salvinorin B: crystal structure and affinity at the κ opioid receptor - Munro, Thomas A (Beilstein-Institut, 2007)
There have been many reports of epimerization of salvinorins at C-8 under basic conditions, but little evidence has been presented to establish the structure of these compounds. We report here the first crystal structure of an 8-epi-salvinorin or derivative: the title compound, 2b. The lactone adopts a boat conformation with the furan equatorial. Several lines of evidence suggest that epimerization proceeds via enolization of the lactone rather than a previously proposed indirect mechanism. Consistent with the general trend in related compounds, the title compound showed lower affinity at the kappa opioid receptor than the natural epimer salvinorin B (2a). The related 8-epi-acid 4b showed no affinity.